2019
DOI: 10.1038/s41467-019-10404-9
|View full text |Cite
|
Sign up to set email alerts
|

H3.3K27M-induced chromatin changes drive ectopic replication through misregulation of the JNK pathway in C. elegans

Abstract: Substitution of lysine 27 with methionine in histone H3.3 is a recently discovered driver mutation of pediatric high-grade gliomas. Mutant cells show decreased levels and altered distribution of H3K27 trimethylation (H3K27me3). How these chromatin changes are established genome-wide and lead to tumorigenesis remains unclear. Here we show that H3.3K27M-mediated alterations in H3K27me3 distribution result in ectopic DNA replication and cell cycle progression of germ cells in Caenorhabditis elegans … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…Thus, the H3.3K27M and H3.1K27M oncohistones have dramatically different effects on Polycomb-regulated domains. This quantitative effect appears to be a conserved property of H3K27M mutant histones, as replication-coupled H3.2K27M oncohistones are more potent inhibitors of H3K27 trimethylation than H3.3K27M oncohistones in C. elegans ( Delaney et al, 2019 ). We further genotyped these cell lines by targeted gene sequencing ( Kuo et al, 2020 ), and identified multiple genetic alterations ( Supplementary file 5 ), including biallelic deletions of the CDKN2A gene in the two H3.1K27M-bearing cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the H3.3K27M and H3.1K27M oncohistones have dramatically different effects on Polycomb-regulated domains. This quantitative effect appears to be a conserved property of H3K27M mutant histones, as replication-coupled H3.2K27M oncohistones are more potent inhibitors of H3K27 trimethylation than H3.3K27M oncohistones in C. elegans ( Delaney et al, 2019 ). We further genotyped these cell lines by targeted gene sequencing ( Kuo et al, 2020 ), and identified multiple genetic alterations ( Supplementary file 5 ), including biallelic deletions of the CDKN2A gene in the two H3.1K27M-bearing cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the H3.3K27M and H3.1K27M oncohistones have dramatically different effects on Polycomb-regulated domains. This quantitative effect appears to be a conserved property of H3K27M mutant histones, as replication-coupled H3.2K27M oncohistones are more potent inhibitors of H3K27 trimethylation than H3.3K27M oncohistones in C. elegans (Delaney et al, 2019). We further genotyped these cell lines by targeted gene sequencing (Kuo et al , 2020), and identified multiple genetic alterations (Supplementary File 5), including biallelic deletions of the CDKN2A gene in the two H3.1K27M-bearing cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…H3K27M showed a strong affinity for methyltransferase EZH2, the catalytic subunit of the PRC2, repressing H3K27me3 and thereby inhibiting PRC2’s enzymatic activity. Among histone H3, H3.3 is a major variant, and the K27M mutation in histone H3.3 (H3.3K27M) has been identified as a driver mutation for DIPGs [ 89 ]. The mutant cells showed decreased levels and altered distribution of H3K27 trimethylation (H3.3K27me3) via multiple mechanisms, including aberrant PRC2 interactions and hampered H3.3K27me3 spreading.…”
Section: Synthetic Lethality In Idh-mutated Tumorsmentioning
confidence: 99%